Comparison of plantar loading patterns on natural grass and artificial turf during various athletic activities - Sultan, O.; Nuhmani, S.; Muaidi, Q. I. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study aimed to investigate the differences in plantar pressure during various athletic activities on natural grass and artificial turf. METHODS: Twenty-one athletes were fitted with properly sized soccer shoes and corresponding F-Scan system insoles and performed walking, running, vertical jumping and cutting activities to the right and left sides on both natural and artificial turf. RESULTS: There were no statistically significant differences between natural grass and artificial turf in peak pressure, maximum force and force-time integral during all the athletic activities (P>0.05). On both turfs, the highest peak pressure and maximum force values occurred during running and cutting to the right, and the highest force-time integral value occurred during cutting to the right. There were no statistically significant differences between the two turfs in peak pressure in the various anatomical regions during any of the athletic activities (P>0.05). The peak pressure was the highest on the first metatarsal and the hallux during all five activities. A clinically meaningful difference between the surfaces in peak pressure on the second to fifth metatarsals was found during walking, indicating more loading on artificial turf than on natural grass. There was more loading on artificial turf than on natural grass during cutting left and at hallux and third toe on natural grass during cutting right. However, these differences were not statistically significant (P>0.05). CONCLUSIONS: The results of this study suggest that it is important to limit or prevent athletes from undertaking certain activities that increase the risk of re-injury during rehabilitation.